Millennial Poetics: A Study of Contemporary Poetry and Its Developing Trends - Bridget L. Sellers (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
As a field of creative practice, poetry evolves constantly, resulting in new poetic forms that stand in stark contrast to those produced even a few decades ago. Nonetheless, due to the prevalent fixation on standards of the past, little to no research has been undertaken to explore and support the latest and most innovative voices in the literary community, leading to the stagnation poetry’s development. By examining the various approaches to defining the current poetic movement, this essay seeks to develop an understanding of the state of the genre and stimulate the momentum of poetry’s evolution. In the essay, I explore contemporary anthologies and digital texts, including those influenced by the internet age, written through twitter, popularized by social media, or constructed through search engines. Further, by viewing the tendencies of contemporary poetry alongside generational studies, my essay culminates in the conclusion that the most innovative digital poetry written today reflects the particular sensibilities of the millennial generation.